KAJIAN STRATEGI KEBIJAKAN PENGEMBANGAN UMKM DI KABUPATEN KUTAI KARTANEGARA - Aini Aini; Bahari Joko Susilo; Arista Damayanti (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2025)
Development UMKM has a very important role in encouraging sustainable regional economic development, especially in Kutai Kartanegara Regency. The purpose of this study is to identify the institutional growth of UMKM, as well as formulate effective policy strategies to strengthen the role of the UMKM sector in improving the local economy. The method used is a descriptive qualitative approach with literature study techniques and secondary data analysis obtained from regional regulatory documents, related agency reports, and official local government statistical data coupled with primary data from interviews and field observations. The research location consists of 7 sub-districts in Kutai Kartanegara Regency representing upstream, middle and downstream areas. The results of the study show an increase the number of UMKM increased significantly from 56,343 units in 2020 to 66,833 units in 2024. However, there are a number of main obstacles that hinder the performance of UMKM, including weak institutional structures, lack of access to capital, lack of optimal human resource competence, lack of business networks, and lack of optimal digitalization. Based on the results of the study, the recommended recommendations are strengthening institutional capacity through training and improving human resource competencies, improving managerial skills, digitalization as an important strategy in market expansion and operational efficiency, and increasing strategic partnerships between business actors and related stakeholders. It is hoped that this study can be a reference in the formulation of local economic development policies based on local needs and potential, as well as the challenges and threats faced by UMKM, as well as encourage the achievement of sustainable and participatory regional development goals.